Minimally Invasive Approach for Combined Cholecystectomy and Total Hysterectomy with LigaSure - İnegöl Gümüş, İlknur; Sürgit, Önder; Simavlı, Serap; Kaygusuz, İkbal (Gynecology Obstetrics & Reproductive Medicine, 2010)
Wide applications of operative laparoscopy can be carried out as combined procedures for multipl pathologies. In single time anesthesia, these combined minimally invasive procedures gives the advantages of lesser pain and morbidity, faster recovery and shorter hospital stay. We report a 58 years old woman treated for uterine myomas and cholelithiasis. The patient underwent laparoscopic total hysterectomy, bilateral salpingo-oopherectomy and laparoscopic cholecystectomy in single session. Procedures were performed with cross-specialty cooperation between a gynecologist and a general surgeon and were completed laparoscopically without intraoperative or postoperative complications. And the patient was discharged 24 hours after the operation.